Chitosan Oligosaccharide Ameliorates Metabolic Syndrome Induced by Overnutrition via Altering Intestinal Microbiota - Wang, Yihua; Liu, Shili; Tang, Di; Dong, Rui; Feng, Qiang (Frontiers in Nutrition, 2021)
Chitosan oligosaccharides (COS) play a prebiotic role in many ways, while its function on microbiota is not fully understood. In this study, the effects of COS on metabolic syndrome were initially investigated by observing changes in the physiological indicators after adding COS to the diet of mice with high fat (group H) and low fat (group L). The results showed that COS markedly inhibited the accumulation of body weight and liver fat induced by high-fat diet, as well as restored the elevated concentration of blood glucose and fasting insulin to normal levels. Next, changes of the murine intestinal microbiota were examined. The results exhibited that COS reduced with-in-sample diversity, while the between-sample microbial diversity enhanced. Specifically, COS enriched Clostridium paraputrificum and Clostridium ramosum in the mice on a high-fat diet, while the abundance of Clostridium cocleatum was reduced. As a comparison, Parabacteroides goldsteinii and Bacteroides uniformis increased their abundance in response to COS in the low-fat diet group. No-ticeably, a large amount of Akkermansia muciniphila was enriched in both high-fat or low-fat diet groups. Among the differential fecal bacteria, Clostridium ramosume was found to have a positive interaction with Faecalibacterim prausnitzii and Clostridium paraputrificum; Clostridium paraputrificum had a positive interactions with Lactococcus chungangensis and Bifidobacterium mongoliense, suggesting that COS probably ameliorate metabolic syndrome through the microbiota in view of the lipid-lowering effects of these interacted bacteria. Furthermore, the gene expression data revealed that COS improved the functions related to intestinal barrier and glucose transport, which could be the trigger and consequence of the variations in gut microbiota induced by COS. Additionally, correlation analysis found that intestinal bacteria are related to physiological parameters, which further supports the mediating role of gut microbiota in the beneficial effect of COS. In summary, our research results provide new evidence for the prebiotic effects of COS.